The Development of Islamic Religious Education at The Prosperity Agency of The Mosque (BKM) At-Taqwa University of Medan Area - Rizki Ananda; Mardianto Mardianto; Hasan Matsum (Nazhruna: Jurnal Pendidikan Islam, 2021)
This study aims to analyze the development of Islamic Religious Education (IRE) at BKM At-Taqwa Mosque, Medan Area University (UMA). The focus of the discussion includes (1) the role of the At-Taqwa Mosque BKM as a center for PAI development at the UMA campus mosque; (2) the process of developing IRE at the UMA campus mosque; and (3) the supporting and inhibiting factors for the development of IRE in BKM At-Taqwa UMA. This study uses a qualitative approach with an analytical descriptive method. The primary data of the research is the mosque management or BKM Masjid At-Taqwa UMA, while the secondary data is the community of the UMA campus. Data collection was obtained by means of observation, interviews, and document studies. Furthermore, the data were analyzed by means of data reduction, data presentation, and drawing conclusions. The results of this study indicate that (1) At-Taqwa Mosque BKM plays an important role in making the campus mosque a center for IRE development on the UMA campus; (2) the process of developing IRE at the UMA campus mosque is carried out in the form of the ta'lim assembly and TPA in the mosque; (3) as for the supporting factors in the development of IRE at BKM At-Taqwa UMA, namely an organized agenda, adequate number of worshipers, cooperation from BKM management, inviting qualified resource persons/lecturers, and funding support sourced from community infaq.